Democratisation of scientific advice. Issue 7478 (2nd December 2004) - Bal, Roland; Bijker, Wiebe E; Hendriks, Ruud
Abstract : Dutch experience shows how scientific advisory bodies can cope with the growing political demands for transparency and lay participation without compromising their function